The use of steel X-bracing combined with shear link to seismically upgrading reinforced concrete frames - Ashraf Osman; Ahmed E. Farouk (Journal of Engineering and Applied Science, 2023)
Abstract This study examines the feasibility of utilizing steel concentrically X-bracing rigidly connected to shear link to retrofit seismically defected reinforced concrete (RC) frames. It involves examining the lateral behavior of two hypothetical frames strengthened using this proposed system, a single story-single bay RC frame, and a five-story RC office building. For the former, both elastic and inelastic push-over analyses were performed to examine the lateral behavior of strengthened and original RC frames, while the original and strengthened five-story frames were analyzed under the action of monotonically increasing lateral loads and nonlinear time histories. In detailing the strengthening scheme, procedure complying with the capacity design concept was adopted whereby the shear links were detailed to yield prior to RC frames structural elements to reduce the demand on them. The stiffnesses, strengths, and plastic hinging formation patterns for original and strengthened frames under the action of different loading conditions were determined and evaluated. Story shears and maximum story displacements were recorded and examined. It was concluded that this system is feasible for seismically strengthening the defected RC frames. Guidelines for detailing this scheme were provided within the context of this research study.